2017
DOI: 10.1002/anie.201703360
|View full text |Cite
|
Sign up to set email alerts
|

Δ‐Myrtoxin‐Mp1a is a Helical Heterodimer from the Venom of the Jack Jumper Ant that has Antimicrobial, Membrane‐Disrupting, and Nociceptive Activities

Abstract: D-Myrtoxin-Mp1a (Mp1a), a4 9-residue heterodimeric peptide from the venom of Myrmecia pilosula, comprises a2 6-mer Achain and a2 3-mer Bchain connected by two disulfide bonds in an antiparallel arrangement. Combination of the individual synthetic chains through aerial oxidation remarkably resulted in the self-assembly of Mp1a as ah omogenous product without the need for directed disulfide-bond formation. NMR analysis revealed aw ell-defined, unique structure containing an antiparallel a-helix pair.D ual polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 22 publications
7
62
0
Order By: Relevance
“…Defensive venoms such as those of bees or fishes are arguably comprised of conserved toxins acting primarily to trigger pain and being less complex in composition than predatory venoms [1]. [28,29,34,36]. Alignments were generated with the Muscle program in Seaview version 4.6.1 and edited using BOXSHADE version 3.2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defensive venoms such as those of bees or fishes are arguably comprised of conserved toxins acting primarily to trigger pain and being less complex in composition than predatory venoms [1]. [28,29,34,36]. Alignments were generated with the Muscle program in Seaview version 4.6.1 and edited using BOXSHADE version 3.2.…”
Section: Discussionmentioning
confidence: 99%
“…The structural prediction performed on the PepFold3 server suggested that all pseudomyrmecitoxins adopt secondary structures dominated by α-helices [35]. [28,29,34,36]. Alignments were generated with the Muscle program in Seaview version 4.6.1 and edited using BOXSHADE version 3.2.…”
Section: Molecular Features Of Pseudomyrmecitoxinsmentioning
confidence: 99%
“…Analysis of the venom of JJA has so far identified four peptides—Myr p 1, Myr p 2 and Myr p 3—that have been recognized as allergens by the International Union of Immunology Societies, and a histamine‐releasing peptide called pilosulin 5. Myr p 1 is a 6067 Da monomer peptide (also called pilosulin 1); Myr p 2 is a 5608 Da heterodimer (also called pilosulin 3 and delta‐Myrtoxin‐Mp1a); Myr p 3 is a 8198 Da homodimer (also called pilosulin 4); pilosulin 5 is a 8546 Da homodimer; all four are highly basic . Multiple isoforms of these peptides have been identified by genetic analysis or mass spectrometry (reviewed in reference), and the three‐dimensional (3D) structure of Myr p 2 has been determined by NMR spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
“…Myr p 1 is a 6067 Da monomer peptide (also called pilosulin 1); Myr p 2 is a 5608 Da heterodimer (also called pilosulin 3 and delta‐Myrtoxin‐Mp1a); Myr p 3 is a 8198 Da homodimer (also called pilosulin 4); pilosulin 5 is a 8546 Da homodimer; all four are highly basic . Multiple isoforms of these peptides have been identified by genetic analysis or mass spectrometry (reviewed in reference), and the three‐dimensional (3D) structure of Myr p 2 has been determined by NMR spectroscopy . A number of components of >20 kDa with IgE‐binding capacity remain to be characterized …”
Section: Introductionmentioning
confidence: 99%
“…Mp1a demonstrates potent cell‐membrane binding and disrupting activity as well as the induction of nonspecific Ca 2+ influx into cells. Synthetic manipulation of the native disulfide‐bond connectivity or separation of the two chains revealed analogues with functional selectivity . In a search for new xenoprotein therapeutics, Bradley Pentelute (MIT, USA) described a high‐throughput approach for the synthesis of xenoprotein/peptide libraries (i.e., proteins and peptides that contain artificial amino acids) by fully automated flow‐based peptide synthesis .…”
Section: Post‐translational Modifications and Artificial Peptides To mentioning
confidence: 99%